Left-wing populism in Spain - I. L. Prokhorenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines formation, evolution and political perspectives of the Spanish radical left-wing populist party ‘We Can!’ (Podemos) in the face of growing support for populism in the the Southern European countries as well as in the European Union in general. The author identiﬁes the origins and country-speciﬁc characteristics of the left-wing populism in Spain and provides the general overview of trends in the country’s party system since the middle of the 2000s, including the growing axiological, generational, political and ideological cleavages in the Spanish divided society. Special attention is paid to the political portrait of the Podemos leader Pablo Iglesias and the prospects for development of political situation in the country after his resignation and subsequent electoral defeat in the Autonomous Community of Madrid in May 2021. As such, this case study can provide some useful insights on the nature of populism in the EU member-states in general. In particular, the paper shows that the fragmentation of traditional political systems and the impacts of the sovereign debt crisis per se do not provide a suﬃcient explanation for the growing demand for populist rhetoric and charismatic leaders, but rather they have exposed certain structural economic and social imbalances. It is exactly these imbalances which traditional political parties are unable to address that create a breeding ground for various left- and right-wing parties and movements. As a result, the author concludes that populism will remain an essential element of political landscape in Spain despite all scandals that accompany populist politicians as the case of Pablo Iglesias has clearly demonstrated. At the same time the author emphasizes that it is this clear and imminent threat posed by the populist movements that may eventually serve as an impetus for a renewal of traditional parties and of the country’s political system in general.